REPORT OF 10 CASES OF VISCERAL LARVA MIGRANS IN IRAN - MB. Rokni; J. Massoud; Gh. Mowlavi (Tehran University of Medical Sciences, 2000)
Toxocariasis or Visceral Larva Migrans (VLM) is a parasitic infection resulting from the invasion of human visceral organs by Nematode larvae of genus Toxocara (dog Ascaris). Using gathered information of clinical manifestations, past history, biochemical and haematological tests, Indirect Fluorescence Antibody test (IFA) and follow up of patients, totally 10 human cases (6 males and 4 females) from 1993 to 1995 were diagnosed. The age of patients was between 3 to 52 years, but the most common age was in age group of 0-9 years old. Most of the patients (7 cases) had a previous history of contact with dog. A history of geophagy and contact with cat were noted in patients 4 & 3, respectively. The residential areas of the patients were Guilan, Tehran, Hamadan, Khuzestan, Zanjan and Mazandaran. All patients showed high peripheral eosinophilia. Leukocytosis, high SGOT, SGPT and serum globulin were observed in 6, 3, 2 and 6 cases, respectively. Clinical findings were pain, fever, anorexia, dizziness, dyspnea, weight loss, cough, hepatomegaly, splenomegaly and lymphadenopathy.